DAMPAK IMPLEMENTASI PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 - Ayu Wahyuni; Cut Shaviatul Bayti; Aufa Rindu Purnama; Lidya Wahyundari (Biogenesis, 2021)
At current, the Covid-19 pandemic is a global health threat with confirmed cases and high mortality. WHO declared this outbreak a global pandemic because the transmission of this virus was very fast and most countries in the world also  exposed to it. Recent data updating the number of confirmed patients worldwide is 23,491,520 positive cases. Indonesia is one of the countries that has been exposed to this virus  the beginning of March until now on 25 August 2020, there were 157,859 confirmed cases spread across 34 provinces and 415 districts / cities. The purpose of this study was to identify the impact the teachers, students and parents felt during the Covid 19 pandemic during the implementation of online learning. This study used a method descriptive analysis content. This method is used to describe some information about the impact of the Covid-19 pandemic on implementing online learning. The results of this study are the impact on teacher performance, that is, the loss of teacher motivation in teaching and there are teachers who do not understand use of electronic devices, the impact on the learning process is that students are not familiar with the distance learning process,Impact on parents as student guardians is issue between students and teachers and economic conditions can affect the learning process of the students.  In the midst of this pandemic, parents are very influential in children's development, such as trying to create a supportive environment to motivate children in learning with these different situations, and the government is expected to participate in embracing the complaints and needs of children in learning, for example internet quotas. Hopefully with joint efforts, the pandemic will end quickly and we can return to building a pleasant situation better than before.